2009
DOI: 10.1016/j.atherosclerosis.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein particle subclasses, cardiovascular disease and HIV infection

Abstract: Both HIV and treatment for HIV have been associated with an increased risk of cardiovascular disease (CVD). Unfavorable lipid changes could offer a possible explanation for the increased risk of CVD. We examined the association of lipoprotein particles with CVD in HIV-infected patients. The Strategies for Management of Anti-Retroviral Therapy (SMART) study was a trial of intermittent use of ART (drug conservation [DC]) versus continuous of ART (viral suppression [VS]). In a nested case-control study, lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 19 publications
6
92
3
3
Order By: Relevance
“…However, and in contrast with our present observations, it has been reported that the concentration of cholesterol in large HDL particles was unaltered in HIV-infected patients as compared with uninfected controls ( 32 ). Interruption of HAART was associated with a reduction in HDL particles of medium and small size ( 35 ), or only in HDL particles of medium size with no change in HDL particles of small size ( 36 ). We presently observed a specifi c reduction of the large HDL2b subfraction in HIV-infected patients when compared with controls.…”
Section: Discussioncontrasting
confidence: 56%
“…However, and in contrast with our present observations, it has been reported that the concentration of cholesterol in large HDL particles was unaltered in HIV-infected patients as compared with uninfected controls ( 32 ). Interruption of HAART was associated with a reduction in HDL particles of medium and small size ( 35 ), or only in HDL particles of medium size with no change in HDL particles of small size ( 36 ). We presently observed a specifi c reduction of the large HDL2b subfraction in HIV-infected patients when compared with controls.…”
Section: Discussioncontrasting
confidence: 56%
“…We could not demonstrate a significant change in the percentage of patients with atherogenic plasma levels of lipoproteins commonly associated with hypertriglyceridemia, such as slightly triglyceride-enriched VLDL and sdLDL-apoB. However, the risk of cardiovascular events in our population remains a concern mainly due to the high percentage of patients with low HDL, 42 frequent smoking, 43 and inflammatory factors associated with HIV infection. 44 …”
Section: Discussionmentioning
confidence: 54%
“…43 This association contributes to the consideration of HIV-infected patients at risk of coronary heart disease (CHD). In contrast, Duprez et al 44 found that, neither VLDL-p nor LDL-p concentrations were associated with CVD. 44 In general it's clear that HIV infection and subsequent treatment interfere with lipid metabolism to increase the possibility of cardiovascular complications for the patients.…”
Section: Nmr-based Metabonomics Of Hiv-infected Biofluidmentioning
confidence: 90%